2023
DOI: 10.1111/bjh.18747
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow microenvironment disruption and sustained inflammation with prolonged haematologic toxicity after CAR T‐cell therapy

Abstract: Summary Mechanisms of prolonged cytopenia (PC) after chimeric antigen receptor (CAR) T‐cell therapy, an emerging therapy for relapsed or refractory diffuse large B‐cell lymphoma, remain elusive. Haematopoiesis is tightly regulated by the bone marrow (BM) microenvironment, called the ‘niche’. To investigate whether alterations in the BM niche cells are associated with PC, we analysed CD271+ stromal cells in BM biopsy specimens and the cytokine profiles of the BM and serum obtained before and on day 28 after CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…48,[50][51][52] The etiology of prolonged cytopenias is not well understood but is likely multifactorial and related to poor bone marrow reserve from disease infiltration and prior treatment, as well as the myelosuppressive effects of lymphodepleting chemotherapy, CRS, infections, and CAR-T cell-associated hematopoietic dysfunction. 48,51,53,54 The CAR-HEMATOTOX score has been developed to predict the risk of prolonged neutropenia, and is comprised of five variables (hemoglobin, platelet count, white blood cell count, C-reactive protein, and ferritin) measured at the start of lymphodepleting chemotherapy. 49 The clinical significance of ICAHT should not be underestimated, as prolonged neutropenia is associated with markedly increased risks of infection and NRM.…”
Section: Prolonged Cytopeniasmentioning
confidence: 99%
See 1 more Smart Citation
“…48,[50][51][52] The etiology of prolonged cytopenias is not well understood but is likely multifactorial and related to poor bone marrow reserve from disease infiltration and prior treatment, as well as the myelosuppressive effects of lymphodepleting chemotherapy, CRS, infections, and CAR-T cell-associated hematopoietic dysfunction. 48,51,53,54 The CAR-HEMATOTOX score has been developed to predict the risk of prolonged neutropenia, and is comprised of five variables (hemoglobin, platelet count, white blood cell count, C-reactive protein, and ferritin) measured at the start of lymphodepleting chemotherapy. 49 The clinical significance of ICAHT should not be underestimated, as prolonged neutropenia is associated with markedly increased risks of infection and NRM.…”
Section: Prolonged Cytopeniasmentioning
confidence: 99%
“…Indeed, persistent severe cytopenias are observed in up to 20%–30% of patients 1 month after CAR‐T cell infusion and in up to 10% beyond 1–2 years 48,50–52 . The etiology of prolonged cytopenias is not well understood but is likely multifactorial and related to poor bone marrow reserve from disease infiltration and prior treatment, as well as the myelosuppressive effects of lymphodepleting chemotherapy, CRS, infections, and CAR‐T cell‐associated hematopoietic dysfunction 48,51,53,54 . The CAR‐HEMATOTOX score has been developed to predict the risk of prolonged neutropenia, and is comprised of five variables (hemoglobin, platelet count, white blood cell count, C‐reactive protein, and ferritin) measured at the start of lymphodepleting chemotherapy 49 .…”
Section: Prolonged Cytopeniasmentioning
confidence: 99%
“…Overall, all studies defined PHT according to the time of occurrence, except for Kato's study, which was based on the duration of PHT 13 . Fried et al defined PHT as any grade of neutropenia, anaemia or thrombocytopenia on Day 21 after CAR‐T‐cell infusion and found that more than 90% of patients experienced prolonged cytopenia 5 ; the incidence of PHT decreased to 78.9% on Day 28 in the Wang cohort 14 and to 66.7% in the Kitamura study 15 . The standard for the severity of PHT in most studies is unresolved grade 3/4 cytopenia.…”
Section: Incidence Of Prolonged Haematologic Toxicity After Car‐t‐cel...mentioning
confidence: 99%
“…ferritin and CRP), and tocilizumab or steroid treatment, 5,27,44 which all indicate that patients with a greater degree of inflammation are more likely to experience PHT. Notably, some studies have discovered an association between cytokines and prolonged cytopenia 15,26,40,41 . These cytokines not only have proinflammatory and immunomodulatory properties but also different functions in haematopoiesis.…”
Section: Mechanisms Of Prolonged Haematologic Toxicitymentioning
confidence: 99%
“…In this issue, Kitamura and colleagues 3 take some steps towards identifying mechanistic markers to predict PC. They demonstrate that BM niche cells are affected by CAR‐T therapy, and importantly that a lower area proportion of CD271+ cells before CAR‐T therapy was associated with an increased rate of PC.…”
mentioning
confidence: 99%